Influence of wheat flour substitution with potato pulp on dough rheology, microstructure and noodle quality. (31st December 2020) - Pu, Huayin; Yue, Miao; Guo, Simin; Li, Yanjun; Yang, Yifei; Kuang, Jiwei; Huang, Junrong
Summary: The effects of potato pulp (0–40%) on dough rheology and microstructures, as well as noodle quality, were investigated in this study. Substitution of wheat flour with potato pulp led to a decrease in β ‐sheet content, an increase in α ‐helix and unordered content for protein in dough, as well as a drop of the storage and loss modulus, which was mainly caused by the weakening of dough gluten strength. Scanning electron microscopy confirmed that the gluten–starch network could no longer to be observed for the formulated dough containing 30–40% potato pulp. Structural damage of dough induced the increases in optimal cooking time, cooking loss and adhesiveness, and a decrease in cohesiveness of cooked noodles. However, the samples with 20% potato pulp addition showed higher values in water absorption, hardness, springiness and chewiness, indicating that noodles with potato pulp content below 20% were acceptable. Abstract : Influence of potato pulp on dough rheology, microstructure and noodle quality